Polyethylene glycol perturbs the unfolding of CRABP I: A correlation between experimental and theoretical approach - Subadini, Suchismita; Bera, Krishnendu; Hritz, Jozef; Sahoo, Harekrushna (Colloids and surfaces. B, Biointerfaces, 2021)
The importance of macromolecules paves the way towards a detailed molecular level investigation as all most all cellular processes occurring at the interior of cells in the form of proteins, enzymes, and other biological molecules are significantly affected because of their crowding. Thus, exploring the role of crowding environment on the denaturation and renaturation kinetics of protein molecules is of great importance. Here, CRABP I (cellular retinoic acid binding protein I) is employed as a model protein along with different molecular weights of Polyethylene glycol (PEG) as molecular crowders. The experimental evaluations are done by accessing the protein secondary structure analysis using circular dichroism (CD) spectroscopy and unfolding kinetics using intrinsic fluorescence of CRABP I at 37 °C to mimic the in vivo crowding environment. The unfolding kinetics results indicated that both PEG 2000 and PEG 4000 act as stabilizers by retarding the unfolding kinetic rates. Both kinetic and stability outcomes presented the importance of crowding environment on stability and kinetics of CRABP I. The molecular dynamics (MD) studies revealed that thirteen PEG 2000 molecules assembled during the 500 ns simulation, which increases the stability and percentage of β-sheet. The experimental findings are well supported by the molecular dynamics simulation results.
Keywords: Protein stabilizer; Kinetics; Crowding agent; Polyethylene Glycols; Protein Denaturation; polyethylenglykoly; Protein Structure, Secondary; Receptors, Retinoic Acid; sbalování proteinů; Circular Dichroism; Protein Folding; sekundární struktura proteinů; Protein unfolding; receptory kyseliny retinové; denaturace proteinů; cirkulární dichroismus; kinetika; PEG; Excluded volume